Lopinavir/ritonavir monotherapy as second-line antiretroviral treatment in resource-limited settings: Week 104 analysis of AIDS clinical trials group (ACTG) A5230 - Kumarasamy N. (Oxford University Press, 2015)
© 2015 The Author. Background. The AIDS Clinical Trials Group (ACTG) A5230 study evaluated lopinavir/ritonavir (LPV/r) monotherapy following virologic failure (VF) on first-line human immunodeficiency virus (HIV) regimens in Africa and Asia. Methods. Eligible subjects had received first-line regimens for at least 6 months and had plasma HIV-1 RNA levels 1000-200 000 copies/mL. All subjects received LPV/r 400/100 mg twice daily. VF was defined as failure to suppress to <400 copies/mL by week 24, or confirmed rebound to >400 copies/mL at or after week 16 following confirmed suppression. Subjects with VF added emtricitabine 200 mg/tenofovir 300 mg (FTC/TDF) once daily. The probability of continued HIV-1 RNA <400 copies/mL on LPV/r monotherapy through week 104 was estimated with a 95% confidence interval (CI); predictors of treatment success were evaluated with Cox proportional hazards models. Results. One hundred twenty-three subjects were enrolled. Four subjects died and 2 discontinued prematurely; 117 of 123 (95%) completed 104 weeks. Through week 104, 49 subjects met the primary endpoint; 47 had VF, and 2 intensified treatment without VF. Of the 47 subjects with VF, 41 (33%) intensified treatment, and 39 of 41 subsequently achieved levels <400 copies/mL. The probability of continued suppression <400 copies/mL over 104 weeks on LPV/r monotherapy was 60% (95% CI, 50%-68%); 80%-85% maintained levels <400 copies/mL with FTC/TDF intensification as needed. Ultrasensitive assays on specimens with HIV-1 RNA level <400 copies/mL at weeks 24, 48, and 104 revealed that 61%, 62%, and 65% were suppressed to <40 copies/mL, respectively. Conclusions. LPV/r monotherapy after first-line VF with FTC/TDF intensification when needed provides durable suppression of HIV-1 RNA over 104 weeks. Clinical Trials Registration. NCT00357552.